Seal characterization and integrity in uplifted basins: Insights from the northern Barents Shelf. (May 2022) - Paulsen, Renate Strugstad; Birchall, Thomas; Senger, Kim; Grundvåg, Sten-Andreas
Abstract: Seal integrity is a key property for petroleum exploration. This is even more the case in uplifted basins, as exemplified by the northern Barents Shelf. Uplift may lead to fracturing, decompaction, gas expansion and fluid flow. Therefore, it is critical to understand the mechanical behaviour of the Jurassic shale caprocks in the Greater Hoop area, where hydrocarbon accumulations are situated as little as 250 m below the seabed. In this contribution we study the Upper Jurassic Fuglen and Hekkingen formations. We analyse the mechanical properties of six wells in the study area in combination with leak-off tests and 3D seismic data to characterise the caprock variability over the area. Ductility appears to be largely a response to total organic content, with overall sealing properties appearing exceptionally good in southern parts but diminishing to the north in the study area due to increasing silt content and thinning of the more organic rich Hekkingen Formation. Highlights: Elastic parameter calculation points towards a two-fold caprock problem in the Hoop Fault complex. Comparing high-resolution seismic data to petrophysical well-data for local and regional varaition within caprocks . Caprocks integrity assessment above ultra-shallow reservoirs. Total Organic Content in shales can increase seal integrity in highly uplifted areas on the northern Barents Shelf.